2007
DOI: 10.1038/sj.bjc.6604045
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin, gemcitabine, and treosulfan in relapsed stage IV cutaneous malignant melanoma patients

Abstract: To evaluate the efficacy of cisplatin, gemcitabine, and treosulfan (CGT) in 91 patients with pretreated relapsed AJCC stage IV cutaneous malignant melanoma. Patients in relapse after first-, second-, or third-line therapy received 40 mg m À2 intravenous (i.v.) cisplatin, 1000 mg m À2 i.v. gemcitabine, and 2500 mg m À2 i.v. treosulfan on days 1 and 8. Cisplatin, gemcitabine, and treosulfan therapy was repeated every 5 weeks until progression of disease occurred. A maximum of 11 CGT cycles (mean, two cycles) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Cisplatin has been widely used for clinical treatment of testicular cancer (Bosl and Motzer, 1997), ovarian carcinomas (Jandial et al ., 2009), head and neck cancer (Khuri et al ., 2000), malignant melanoma (Atzpodien et al ., 2007), lung cancer (Winton et al ., 2005) and breast cancer (Decatris et al ., 2004). However, severe adverse effects, in particular acute renal failure, limit the dose that can be given and consequently prevent more efficient treatment with higher doses (Nagai et al ., 1996; Mathe et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin has been widely used for clinical treatment of testicular cancer (Bosl and Motzer, 1997), ovarian carcinomas (Jandial et al ., 2009), head and neck cancer (Khuri et al ., 2000), malignant melanoma (Atzpodien et al ., 2007), lung cancer (Winton et al ., 2005) and breast cancer (Decatris et al ., 2004). However, severe adverse effects, in particular acute renal failure, limit the dose that can be given and consequently prevent more efficient treatment with higher doses (Nagai et al ., 1996; Mathe et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Of significance, multiple studies have reported the abilities of PAFR antagonists to control the growth of cancer cells or augment the responses of therapeutic agents. 26,29,30 Given that gemcitabine chemotherapy used against multiple human malignancies either alone or in combination with other agents, exhibits adverse effects, including skin rash/necrosis, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] our current studies sought to determine the potential role of MVP release in the pathologic effects of topical gemcitabine application. To that end, pharmacologic approaches using human skin explants and genetic approaches using murine skin were used as relevant models.…”
Section: Discussionmentioning
confidence: 99%
“…Given that gemcitabine chemotherapy used against multiple human malignancies either alone or in combination with other agents, exhibits adverse effects, including skin rash/necrosis, 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 our current studies sought to determine the potential role of MVP release in the pathologic effects of topical gemcitabine application. To that end, pharmacologic approaches using human skin explants and genetic approaches using murine skin were used as relevant models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations